Antonios Finitsis (ed.), Dress and Clothing… in the Hebrew Bible . “For all Her Household are Clothed in Crimson” (Library of Hebrew Bible/Old Testament Studies 679; London – New York – Oxford – New Delhi – Sydney: Clark 2019) - Rambiert-Kwaśniewska, Anna (The Biblical Annals, 2021)
Book review: Antonios Finitsis (ed.), Dress and Clothing… in the Hebrew Bible . “For all Her Household are Clothed in Crimson” (Library of Hebrew Bible/Old Testament Studies 679; London – New York – Oxford – New Delhi – Sydney: Clark 2019). Pp. 191. $ 89.52. ISBN 978-0-5676-8640-4.